2020
DOI: 10.1002/hep.31120
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation Between MYC and β‐Catenin in Liver Tumorigenesis Requires Yap/Taz

Abstract: BaCKgRoUND aND aIMS: Activation of MYC and catenin beta-1 (CTNNB1, encoding β-catenin) can co-occur in liver cancer, but how these oncogenes cooperate in tumorigenesis remains unclear. appRoaCH aND ReSUltS: We generated a mouse model allowing conditional activation of MYC and WNT/ β-catenin signaling (through either β-catenin activation or loss of APC-adenomatous polyposis coli) upon expression of CRE recombinase in the liver and monitored their effects on hepatocyte proliferation, apoptosis, gene expression p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 55 publications
2
49
1
Order By: Relevance
“…MYC has been shown to be a target of b-catenin; however, as shown in a recent study, 21 there was no correlation between transposon-driven CTNNB1 mRNA levels and levels of MYC or MYC targets ( Figure 5A; Supplementary Figure 5A). Surprisingly, there was a significant positive correlation between transposon-driven MYC mRNA levels and b-catenin canonical targets, whereas there was no correlation with b-catenin liver-specific targets ( Figure 5A; Supplementary Figure 5A).…”
Section: Intertumor Heterogeneity Is Shaped By Oncogene Expression Lementioning
confidence: 62%
See 1 more Smart Citation
“…MYC has been shown to be a target of b-catenin; however, as shown in a recent study, 21 there was no correlation between transposon-driven CTNNB1 mRNA levels and levels of MYC or MYC targets ( Figure 5A; Supplementary Figure 5A). Surprisingly, there was a significant positive correlation between transposon-driven MYC mRNA levels and b-catenin canonical targets, whereas there was no correlation with b-catenin liver-specific targets ( Figure 5A; Supplementary Figure 5A).…”
Section: Intertumor Heterogeneity Is Shaped By Oncogene Expression Lementioning
confidence: 62%
“…In a recent study, MYC and b-catenin were shown to cooperate in HCC through the Hippo pathway. 21 We previously showed that cooperation between MYC and b-catenin promotes immune escape and resistance to anti-programmed cell death protein 1 (PD-1) immunotherapy in an immunogenic mouse model of HCC, 14 a result that has been validated in patients. 19,25 In the current study, several of the models, including MYC;CTNNB1 with high levels of MYC, presented tumors that were enriched in the "immune class" signature, 19 which is present in human HCC tumors that could potentially respond to immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, research on YAP1 has increased, especially with respect to tumors. YAP1 has been confirmed to be overexpressed in a variety of tumors, including gastric tumors ( An et al, 2020 ), liver tumors ( Bisso et al, 2020 ), ovarian cancer ( Munoz-Galvan et al, 2020 ), and breast cancer ( Song et al, 2018 ), suggesting that YAP1 has a role as a candidate oncogene in tumorigenesis. In addition, YAP1 also plays an important role in the migration and invasion of melanoma and osteosarcoma ( Zucchini et al, 2019 ; Luo et al, 2020 ).…”
Section: Basic Structure and Functions Of Yap1mentioning
confidence: 99%
“…Previous studies reported YAP as a crucial oncogene in HCC development ( 39 41 ). Moreover, Andrea Bisso et al., demonstrated that YAP mediated the cooperation between MYC and β-Catenin and facilitated liver tumorigenesis ( 42 ). Wenbo Ma et al., also found that histone methyltransferase G9a promoted cholangiocarcinogenesis via YAP ( 43 ).…”
Section: Discussionmentioning
confidence: 99%